Should we screen and treat for bacterial vaginosis (BV) in asymptomatic patients at risk for preterm labor?. Issue 7 (July 2018) - White, Andreia; Waits, Shelley; Rodriguez, Daniela; Hyer, Laura; Hurst, Daniel J.
Abstract : EVIDENCE‐BASED ANSWER : No. Treatment of BV in a mixed group of symptomatic and asymptomatic women with BV does not decrease the rate of preterm birth, even in women with a history of previous preterm birth. Additionally, empiric treatment of BV in women with various risk factors for preterm birth does not decrease rate of preterm birth, nor does screening for and treating BV in asymptomatic women with positive fetal fibronectin (SOR: A, meta‐analyses of RCTs).